Keeping Your Headcount When All About You Are Losing Theirs: Downsizing, Voluntary Turnover Rates, and The Moderating Role of HR Practices - Trevor, Charlie O.; Nyberg, Anthony J. (Academy of Management Journal, 2008)
Although both downsizing and voluntary turnover have been topics of great interest in the organizational literature, little research addresses the topics' possible relationship. Using organization-level data from multiple industries, we first investigate whether downsizing predicts voluntary turnover rates. Second, to support our causal model, we examine whether aggregated levels of organizational commitment mediate this relationship. Third, we test whether the downsizing-turnover rate relationship is (1) mitigated by HR practices that either embed employees in their organization or convey procedural fairness and (2) strengthened by HR practices that enhance career development. Results support the hypothesized main, mediated, and moderated effects.